Shear mechanisms during cryogenic treatment of Ti6Al4V - Ramdan, R.D.; Jauhari, I.; Izman, S.; Abdul Kadir, M.R.; Prawara, B.; Hadi, N. (2011)
Cryogenic treatment has been widely accepted as a method to improve wear properties of tool steel. However, very limited knowledge can be found in the literature regarding its mechanism and application to other metals. This paper describes shear effects during cryogenic treatment on Ti6Al4V alloy compared with cold rolling process. Cryogenic treatment was conducted by heating the alloy up to 950oC followed with cooling process using liquid nitrogen spraying. Optical and scanning electron microscope observation show that elongated primary α phase and shear band width below 4 μm were observed in both cryogenic and cold rolled sample. However both elongated α phase structure and shear band width are finer in the cold-rolled sample which is an indication that shear effect is higher in this sample. In addition, as observed by X-ray diffraction peak calculation using Mud-Master computer program, movement of atom during cryogenic treatment is more intense in the direction parallel with the basal plane, which is the slip plane for hexagonal α phase of titanium alloy. From the above observations it can be concluded that cryogenic treatment on Ti6Al4V has a strong relation with the mechanism of plastic deformation in general.